İlköğretim Okullarında Öğretmenlerin İletişim Kurma Düzeyleri ile Yöneticilerin Destekleyici Liderlik Rolleri Arasındaki İlişki - Çankaya, İ.Halil; Aküzüm, Cemal (Dicle Üniversitesi, 2010)
Bu araştırmanın amacı, sınıf öğretmenlerinin algılarına göre okul içerisindeki iletişim kurma düzeyleri ile yöneticilerinin destekleyici liderlik rolleri arasındaki ilişkiyi incelemektir. Araştırma tarama modeline dayalı bir araştırmadır. Araştırmanın çalışma evrenini Elazığ İl merkezinde 2008–2009 eğitim-öğretim yılı bahar döneminde görev yapan 1500 sınıf öğretmeni oluşturmaktadır. Araştırmanın örneklemi, mevcut evren içerisinde dağıtılan 460 ölçeğe cevap veren 387 kişiden oluşmaktadır. Araştırmada kullanılan destekleyici liderlik ölçeği Hoy (1991) tarafından, iletişim yeterliliği ölçeği ise Jorado vd (2006) tarafından geliştirilmiştir. Araştırmada değişkenler arasındaki ilişki, SPSS 13 programında doğrusal regresyon ve basit korelasyon analizleri ile saptanmıştır. Araştırmada, okul yöneticilerinin destekleyici liderlik rolleri ile öğretmenlerin iletişim yeterlilikleri arasında pozitif bir ilişki olduğu ve öğretmenlerin algıladıkları destekleyici liderlik rollerinin iletişim düzeyini anlamlı yordadığı saptanmıştır

The aim of this research is analyze according to class teachers’ perceived relationship between communication level of classroom teachers and school managers’ supportive leadership rolies in schools. This research has been conducted based on screening model. Sampling of this research consists of classroom teachers working in Elazığ city center during 2008–2009fall education term. The sampling of research is 460 composed of 387 teachers employed within the present population. In research supportive leadership scale It was developed by Hoy (1991) and communication competence scale developed by Jurado et all (2006). In this research the data obtained from the answers given by teachers were analyzed by SPSS 13 data analysis program and findings related to correlation matrix of variables and linear simple regression analysis have been detected. According to correlation bond between variables there is a meaningful and pozitive relationship between school managers’ supportive leadership and teachers’ communication level. According to simple linear regression analysis’ result it has been found out that perceived supportive leadership of teachers directed to school predicts communication skills meaningfully
The Relationship between Teachers’ Communication Competence and Managers’ Supportive Leadership Roles in Primary Schools